Twitter, Political Communication, and Voter Behaviour in Nigeria - Okunade Joshua Kayode; Abdullahi Aliyu Maiwada; Joseph Ifeoluwa Joy (Polit Journal Scientific Journal of Politics, 2026)
The emergence of social media has transformed political communication and electoral campaigns across democratic societies, providing political actors and citizens with new avenues for information dissemination, engagement, and participation. Specifically, the study investigated the role of Twitter in political communication, assessed its impact on voter decision-making and electoral participation, and explored public perceptions of media coverage during the election period. Guided by the Agenda-Setting Theory, the study adopted a qualitative research approach utilizing secondary data. The paper argues that Twitter emerged as a major source of political information for many voters, providing real-time updates, campaign messages, and political discussions. The study found that exposure to political content on Twitter significantly influenced voters' awareness of candidates, perceptions of political issues, and electoral choices. Participants also acknowledged the platform's capacity to enhance political engagement and participation, although concerns were raised regarding misinformation, political bias, and the credibility of some online content. Furthermore, the findings indicated that social media played a more prominent role in informing voters than some traditional media outlets during the election period. The study concludes that Twitter has become a critical instrument of political communication and electoral mobilization in Nigeria's evolving democratic landscape. While the platform contributes to political awareness and citizen participation, there is a need for greater media literacy, ethical journalism, and effective regulation of misinformation to strengthen democratic processes.